PENGARUH PEMERIKSAAN PAJAK, PENAGIHAN PAJAK DAN KEPATUHAN WAJIB PAJAK TERHADAP PENERIMAAN PAJAK DI KOTA BATAM - margaretta, selly; Banjarnahor, Haposan (LPPM Universitas Putera Batam, 2021)
Tax is the greatest income source and revenue in financing development of Indonesia. Optimizing tax receipts cannot be relied upon by the roles of the Director General of Taxes or tax officials, but also the active role of taxpayers. The study aims to discover empirical evidence of the impact of tax audits, tax collections and taxpayer compliance on tax revenue. 100 respondents were invloved in this study as sample. Primary data used in the study obtained by conducting a survey to respondendts with questionnaires distribution. The data collected in this study is multiple linear regression analysis with the help of SPSS. The output indicates that tax audits, tax collections and taxpayer compliance simoultaneously impact on tax revenue. Tax audits has no impact on tax revenue. Tax collection has impact on tax revenue. Taxpayer compliance has impact on tax revenue.